Global employment trends for women (Geneva, 2012)
"Women face particular challenges both in terms of the sectors in which they wish to work as well as the conditions they work under. Promoting gender equality and empowering women is vital to achieving decent work for all and finally stamping out the discrimination that has plagued labour markets. This publication considers a wide variety of quantitative data collected from around the globe, organizing it into a format that projects the causes and effects of gender-related employment trends. It also analyses policy considerations that affect gender and employment. The Global Employment Trends for Women 2012 report focuses on the gender dimensions of labour underutilization and gender inequalities. As the global jobs crisis continues unabated, the report analyses trends in employment opportunities and the extent of unemployment, but it is also concerned with developments in employment quality. To this end, the report analyses recent trends and gender gaps in different employment categories, including sectoral and occupational segregation in labour markets. It also illustrates the main factors at the household level that influence female labour market outcomes, presents examples of good practices and highlights key policy areas for reducing gender-based inequalities around the world."